The Relationship of Life Expectancy, Attitude towards Delinquent Behavior, and Experience of Drug Abuse among Male Senior High School Students of Shirabad and Downtown of Zahedan - Ali Arab (مطالعات روانشناسی تربیتی, 2017)
Adolescence is one of the most sensitive and most critical periods of human growth, because due to the instability in mental status the individual decisions may lead to risky behaviors. The main aim of study was investigating the relationship of life expectancy, attitude towards delinquent behavior, and experience of drug abuse among male senior high school students in Shirabad suburban area and downtown of Zahedan. The objective of study was to compare the variables of this study among the students  of Shirabad area and downtown. The method of this study was descriptive, correlational designs. The statistical population included all students in Shirabad and schools of district 2 in downtown. Among them, using the cluster random sampling method, 200 students were selected (100 students in Shirabad and 100 students in downtown). The measurement tools were the Fazli Attitude towards Delinquent Behaviors Questionnaire (2010) and the Miller & Powers Hope Scale (1998). To analyze the obtained data Pearson correlation coefficient, regression analysis and independent t-test were used. The results of this study showed that life expectancy was significantly and positively related to negative attitude towards delinquent behavior, moreover, life expectancy was significantly and diversely correlated with positive attitude towards delinquent behavior (p≥0.001). In addition, the results of regression analysis showed that the life expectancy explains respectively 29, 6 and 33 percent of the variance of experience of drug abuse, positive attitude towards delinquent behavior and nagative attitude towards delinquent behavior. Moreover, the results of study revealed that there is a significant difference between the students of Shirabad and the students of downtown regarding the experience of drug abuse, negative and positive attitude towards the delinquent behavior and life expectancy (p≥0.001). Considering the results of this study it is recommended to hold workshops and trainings to improve mental and physical health of students by increasing hope and life expectancy.